Shedding of dust rims in chondrule collisions in the protoplanetary disc - Umstätter, Philipp; Gunkelmann, Nina; Dullemond, Cornelis (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Dust rims covering chondrules may strongly influence their collision dynamics. We use granular-mechanics simulation to analyse in detail such collisi